Conductive particles, conductive material, and connection structure

By placing a Ni-Sn conductive layer with low tin content on the conductive particles and forming protrusions, combined with the adhesive resin, the connection resistance of conductive particles in the prior art under high temperature, high humidity and high voltage environments is solved. High and metal corrosion problems achieve higher conduction reliability and insulation reliability.

CN119173960APending Publication Date: 2024-12-20SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380041970.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-08
Filing Date
2023-07-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing conductive particles are prone to increased connection resistance and metal corrosion in high temperature, high humidity and high voltage environments, resulting in reduced conduction reliability, especially in acidic environments, which is difficult to effectively reduce connection resistance.

Method used

The Ni-Sn conductive layer arranged on the substrate particles has an overall tin content of less than 5% by weight. The maximum tin content in the 1/2 area outside the conductive layer is determined to be more than 5% by weight by TEM-EDX, and the conductive layer is carried out. A plurality of protrusions are formed on the outer surface of the layer, and a conductive material is formed in combination with an adhesive resin.

Benefits of technology

It effectively reduces the connection resistance between electrodes, and prevents charge movement in the Ni-Sn conductive layer under high temperature, high humidity and high voltage environments, improving conduction and insulation reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173960A_ABST
    Figure CN119173960A_ABST
Patent Text Reader

Abstract

Provided are conductive particles which, when electrically connected between electrodes, are capable of reducing connection resistance, and which are capable of preventing the movement of charges in a Ni-Sn conductive layer even when exposed to a high voltage for a long period of time in a high-temperature, high-humidity environment. This conductive particle is provided with a base particle and an Ni-Sn conductive layer containing nickel and tin, the Ni-Sn conductive layer is disposed on the surface of the base particle, the average content of tin in the entire region of the Ni-Sn conductive layer is less than 5% by weight, and when the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the average content of tin in the thickness direction of the Ni-Sn conductive layer is less than 5% by weight. The maximum value of the tin content is 5% by weight or more in a region of 1 / 2 of the thickness of the outside of the Ni-Sn conductive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to conductive particles having substrate particles and a conductive layer disposed on the surface of the substrate particles. In addition, the present invention relates to a conductive material and a bonded structure using the conductive particles. Background Art

[0002] Anisotropic conductive materials such as anisotropic conductive pastes and anisotropic conductive films are widely known. In the anisotropic conductive materials, conductive particles are dispersed in a binder resin. In addition, conductive particles having a substrate particle and a conductive portion disposed on the surface of the substrate particle are used as the conductive particles.

[0003] The anisotropic conductive material is used to obtain various connection structures. Examples of the connection using the anisotropic conductive material include connection between a flexible printed circuit board and a glass substrate (FOG (Film on Glass)), connection between a semiconductor chip and a flexible printed circuit board (COF (Chip on Film)), connection between a semiconductor chip and a glass substrate (COG (Chip on Glass)), and connection between a flexible printed circuit board and a glass epoxy substrate (FOB (Film on Board)).

[0004] When the conductive particles are exposed to the presence of an acid, corrosion of the conductive layer containing nickel or the like may occur. In addition, when such conductive particles are used to connect electrodes to obtain a connection structure, when the connection structure is exposed to the presence of an acid, the connection resistance between the electrodes may increase. For such reasons, the development of conductive particles that are not prone to corrosion of the conductive layer even when exposed to an acid has been studied.

[0005] As an example of the conductive particles, Patent Document 1 below discloses a conductive particle comprising: a substrate particle, and a conductive layer disposed on the surface of the substrate particle and containing nickel. In the conductive particles, the melting point of the conductive layer containing nickel is 300° C. or higher. In the conductive particles, the conductive layer containing nickel is an alloy layer containing nickel and tin, and the average content of tin in the entire 100% by weight of the conductive layer containing nickel is 5% by weight or more and 50% by weight or less.

[0006] Patent Document 2 below discloses conductive particles, which include: substrate particles, and a conductive layer disposed on the surface of the substrate particles and containing nickel, wherein the conductive layer containing nickel is an alloy layer containing nickel, tin, and indium. In the conductive particles, the average content of tin and indium in total is less than 5% by weight in 100% by weight of the region from the outer surface of the conductive layer containing nickel to the inner side to 1 / 2 of the thickness.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2015-130328

[0010] Patent Document 2: WO2017 / 138521A1 Summary of the invention

[0011] Technical problem solved by the invention

[0012] In recent years, conductive materials used in wearable displays such as smart watches and smart glasses, various sensors, etc. have attracted attention. Wearable displays are based on the premise of long-term continuous use in various environments, so the conductive particles and connection structures used in wearable displays are required to have performance that can withstand long-term exposure to high temperature, high humidity and high voltage.

[0013] When the electrodes are electrically connected to obtain a connection structure using the conventional conductive particles described in Patent Document 1, the average tin content is high, so the connection resistance is high. In addition, when conductive particles exposed to high temperatures are used or a connection structure using conductive particles is exposed to high temperatures, there is a problem that the connection resistance is easily increased.

[0014] On the other hand, when the conductive particles containing a very small amount of tin described in patent document 2 are used to obtain a connection structure, the initial connection resistance and the connection resistance in the presence of a low concentration of acid can be relatively reduced, but in the presence of a higher concentration of acid, it is difficult to fully reduce the connection resistance. In addition, when the conductive particles described in patent document 2 are exposed to high voltage for a long time under a high temperature and high humidity environment, metal corrosion sometimes occurs, and the charge of the conductive layer moves. As a result, a short circuit may occur, reducing the conduction reliability.

[0015] The object of the present invention is to provide a conductive particle which can reduce the connection resistance when the electrodes are electrically connected, and can prevent the movement of charges in the Ni-Sn conductive layer even when exposed to high voltage for a long time in a high temperature and high humidity environment. In addition, the object of the present invention is to provide a conductive material and a connection structure using the conductive particle.

[0016] Technical means of solving problems

[0017] According to a broad scheme of the present invention, there is provided a conductive particle comprising: a substrate particle, and a Ni—Sn conductive layer comprising nickel and tin, wherein the Ni—Sn conductive layer is arranged on the surface of the substrate particle, the average content of tin in the entire region of the Ni—Sn conductive layer is less than 5% by weight, and when the content of tin in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, the maximum value of the tin content in the region of 1 / 2 of the thickness on the outside of the Ni—Sn conductive layer is 5% by weight or more.

[0018] In a specific embodiment of the conductive particle of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, 80% by weight or more of tin out of a total of 100% by weight of tin contained in the entire Ni—Sn conductive layer is contained in a region of 1 / 2 thickness outside the Ni—Sn conductive layer.

[0019] In a specific aspect of the conductive particle of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, tin is contained in a region accounting for 15% or more of the thickness of the Ni—Sn conductive layer.

[0020] In a specific embodiment of the conductive particle of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, the Ni—Sn conductive layer contains tin at a content of 5 wt % or more in a region of 10% or more and less than 50% of the thickness.

[0021] In a specific embodiment of the conductive particles of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, tin is contained at a content of 5 weight % or more in a region of 10% or more and less than 50% of the thickness of the Ni—Sn conductive layer, and the maximum value of the tin content in a region of 1 / 2 of the thickness on the outside of the Ni—Sn conductive layer is 5 weight % or more and 40 weight % or less.

[0022] In a specific aspect of the conductive particle of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, the Ni—Sn conductive layer contains tin at a content of 5 wt % or more in a region that is 30% or less of the thickness.

[0023] In a specific embodiment of the conductive particle of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, the maximum tin content in a region having a thickness of 1 / 2 outside the Ni—Sn conductive layer is 10 wt % or more.

[0024] In a specific embodiment of the conductive particles of the present invention, when the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, tin is contained at a content of 5 weight % or more in a region of 30% or less of the thickness of the Ni—Sn conductive layer, and the maximum value of the tin content in a region of 1 / 2 of the thickness on the outside of the Ni—Sn conductive layer is 10 weight % or more.

[0025] In a specific aspect of the conductive particle of the present invention, the conductive particle has a particle diameter of 0.1 μm or more and 1000 μm or less.

[0026] In a specific aspect of the conductive particle according to the present invention, the conductive particle has a plurality of protrusions on the outer surface of the Ni—Sn conductive layer.

[0027] According to a broad aspect of the present invention, a conductive material includes the conductive particles and a binder resin.

[0028] According to a broad scheme of the present invention, there is provided a connection structure comprising: a first connection object part having a first electrode on its surface; a second connection object part having a second electrode on its surface; and a connection portion connecting the first connection object part and the second connection object part, wherein the connection portion is formed by the conductive particles or by a conductive material comprising the conductive particles and a binder resin, and the first electrode and the second electrode are electrically connected via the conductive particles.

[0029] Effects of the Invention

[0030] The conductive particles of the present invention are provided with: substrate particles, and a Ni-Sn conductive layer containing nickel and tin. In the conductive particles of the present invention, the Ni-Sn conductive layer is arranged on the surface of the substrate particles, and the average content of tin in the entire region of the Ni-Sn conductive layer is less than 5% by weight. In the conductive particles of the present invention, when the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the content of tin in the region of 1 / 2 of the thickness outside the Ni-Sn conductive layer is 5% by weight or more. In the conductive particles of the present invention, since the above-mentioned structure is provided, when the conductive particles of the present invention are used to electrically connect between electrodes, the connection resistance can be reduced, and even if the conductive particles of the present invention are exposed to high voltage for a long time in a high temperature and high humidity environment, the movement of charges in the Ni-Sn conductive layer can be prevented. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] [ Figure 1 ] Figure 1 This is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.

[0032] [ Figure 2 ] Figure 2 It is a cross-sectional view showing the conductive particles according to the second embodiment of the present invention.

[0033] [ Figure 3 ] Figure 3 It is a cross-sectional view which shows the electroconductive particle which concerns on 3rd Embodiment of this invention.

[0034] [ Figure 4 ] Figure 4 It is a schematic diagram for demonstrating each area|region of the Ni-Sn conductive layer in the conductive particle which concerns on 1st Embodiment of this invention.

[0035] [ Figure 5 ] Figure 5 This is a cross-sectional view schematically showing a connection structure using conductive particles according to the first embodiment of the present invention. DETAILED DESCRIPTION

[0036] Hereinafter, the details of the present invention will be described.

[0037] (Conductive particles)

[0038] In the past, when the conductive layer contained nickel, nickel was easily corroded, so when nickel was precipitated, the connection resistance between the electrodes tended to increase. In addition, when the conductive particles containing nickel in the conductive layer were exposed to high voltage under high temperature and high humidity, metal corrosion sometimes occurred, and the charge of the conductive layer moved. As a result, short circuits sometimes occurred, reducing the conduction reliability.

[0039] The present inventors have studied a conductive particle, which can reduce the initial connection resistance and the connection resistance after exposure to the presence of acid even if it contains nickel, and can suppress the movement of charges in the conductive layer even if the conductive particle is exposed to high voltage for a long time in a high temperature and high humidity environment. As a result of in-depth research, the present inventors focused on the content and distribution of tin in the conductive layer. The present inventors solved the problem by suppressing the tin content of the entire conductive layer and studying the distribution of tin in the conductive layer.

[0040] The conductive particles of the present invention include: a substrate particle, and a Ni-Sn conductive layer containing nickel and tin, wherein the Ni-Sn conductive layer is disposed on the surface of the substrate particle. In the conductive particles of the present invention, the average content of tin in the entire region of the Ni-Sn conductive layer is less than 5% by weight. In the conductive particles of the present invention, when the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the content of tin in the region of 1 / 2 thickness outside the Ni-Sn conductive layer is 5% by weight or more.

[0041] By adopting the above-mentioned structure in the conductive particles of the present invention, when the conductive particles of the present invention are used to make electrical connections between electrodes, the initial connection resistance can be reduced. In addition, the connection resistance after exposure to the presence of acid can be reduced. In addition, even if the conductive particles are exposed to high voltage (e.g., 15V) for a long time (e.g., 500 hours) under high temperature (e.g., 85°C) and high humidity (e.g., 85%RH), the movement of charges in the Ni-Sn conductive layer can be prevented.

[0042] In the present invention, when a connection structure is prepared using conductive particles stored under a high-temperature and high-humidity environment for a long period of time, an increase in connection resistance can be suppressed.

[0043] The particle size of the conductive particles is preferably 0.1 μm or more, more preferably 1 μm or more, and preferably 1000 μm or less, more preferably 500 μm or less, further preferably 100 μm or less, and particularly preferably 30 μm or less. When the particle size of the conductive particles is above the lower limit and below the upper limit, when the conductive particles are used to connect electrodes, the contact area between the conductive particles and the electrodes becomes large enough, and it is not easy to form condensed conductive particles when forming the conductive portion. In addition, the interval between the electrodes connected by the conductive particles will not become too large, and the conductive portion becomes difficult to peel off from the surface of the substrate particles.

[0044] The particle diameter of the conductive particles means the diameter when the conductive particles are in a perfect spherical shape. When the conductive particles are in a shape other than a perfect spherical shape, it means the diameter when a perfect spherical shape corresponding to the volume is assumed.

[0045] As for the particle size of the conductive particles, the average particle size is preferred, and the number average particle size is preferred. As for the particle size of the conductive particles, for example, 50 arbitrary conductive particles are observed under an electron microscope or an optical microscope, and the average value of the particle size of each conductive particle is calculated; or it is obtained using a particle size distribution measuring device. In the observation under an electron microscope or an optical microscope, the particle size of each conductive particle is obtained as the particle size under the equivalent diameter of a circle. In the observation under an electron microscope or an optical microscope, the average particle size under the equivalent diameter of a circle of any 50 conductive particles is approximately equal to the average particle size under the equivalent diameter of a sphere. In the particle size distribution measuring device, the particle size of each conductive particle is obtained as the particle size under the equivalent diameter of a sphere. The average particle size of the conductive particles is preferably calculated using a particle size distribution measuring device.

[0046] The coefficient of variation (CV value) of the particle size of the conductive particles is preferably 10% or less, more preferably 5% or less. When the coefficient of variation of the particle size of the conductive particles is below the upper limit, the conduction reliability and insulation reliability between electrodes can be further effectively improved. The lower limit of the coefficient of variation of the particle size of the conductive particles is not particularly limited. The coefficient of variation of the particle size of the conductive particles may be 0%, may be above 0%, or may be above 5%.

[0047] The coefficient of variation (CV value) can be determined in the following manner.

[0048] CV value (%) = (ρ / Dn) × 100

[0049] ρ: Standard deviation of particle size of conductive particles

[0050] Dn: average value of particle size of conductive particles

[0051] The shape of the conductive particles is not particularly limited. The conductive particles may be spherical, or may be other than spherical, or may be flat.

[0052] Hereinafter, specific implementation modes and embodiments of the present invention will be described with reference to the accompanying drawings to make the present invention clear. It should be noted that in the accompanying drawings, for the convenience of illustration, the dimensions and thicknesses are appropriately changed according to the actual dimensions and thicknesses.

[0053] Figure 1 This is a cross-sectional view showing the conductive particles according to the first embodiment of the present invention.

[0054] Figure 1 The conductive particle 1 shown has a substrate particle 2 and a Ni—Sn conductive layer 3. The Ni—Sn conductive layer 3 contains nickel and tin. The Ni—Sn conductive layer 3 is disposed on the surface of the substrate particle 2. In the first embodiment, the Ni—Sn conductive layer 3 is in contact with the surface of the substrate particle 2. The conductive particle 1 is a coated particle in which the surface of the substrate particle 2 is coated with the Ni—Sn conductive layer 3.

[0055] In the conductive particle 1, the Ni-Sn conductive layer 3 is a single-layer conductive layer. In the conductive particle, the Ni-Sn conductive layer may cover the entire surface of the substrate particle, or the Ni-Sn conductive layer may cover a portion of the surface of the substrate particle. The conductive particle may have a conductive layer other than the Ni-Sn conductive layer. The conductive particle may have a plurality of conductive layers.

[0056] The conductive particle 1 is different from the conductive particles 11 and 21 described below and does not have a core material. The conductive particle 1 does not have a protrusion on the surface. The conductive particle 1 is spherical. The Ni-Sn conductive layer 3 does not have a protrusion on the outer surface. In this way, the conductive particle of the present invention may not have a protrusion on the surface of the Ni-Sn conductive layer and may be spherical. In addition, the conductive particle 1 is different from the conductive particles 11 and 21 described below and does not have an insulating material. However, the conductive particle 1 may have an insulating material disposed on the outer surface of the Ni-Sn conductive layer 3.

[0057] In the conductive particle 1, the average tin content in the entire region of the Ni—Sn conductive layer 3 is less than 5 wt %. In the conductive particle 1, when the tin content in the thickness direction of the Ni—Sn conductive layer 3 is measured by TEM-EDX, the maximum value of the tin content in the region of 1 / 2 thickness outside the Ni—Sn conductive layer 3 is 5 wt % or more.

[0058] Figure 2 It is a cross-sectional view showing the conductive particles according to the second embodiment of the present invention.

[0059] Figure 2 The conductive particles 11 shown include substrate particles 2, a Ni—Sn conductive layer 12, a plurality of core substances 13, and a plurality of insulating substances 14. The Ni—Sn conductive layer 12 is disposed on the surface of the substrate particle 2 so as to be in contact with the substrate particle 2.

[0060] In the conductive particles 11, the Ni-Sn conductive layer 12 is a single-layer conductive layer. In the conductive particles, the Ni-Sn conductive layer may cover the entire surface of the substrate particles, or the Ni-Sn conductive layer may cover a portion of the surface of the substrate particles. The conductive particles may have a conductive layer other than the Ni-Sn conductive layer. The conductive particles may have multiple conductive layers.

[0061] The conductive particle 11 has a plurality of protrusions 11a on the surface. The Ni-Sn conductive layer 12 has a plurality of protrusions 12a on the outer surface. A plurality of core materials 13 are arranged on the surface of the substrate particle 2. The plurality of core materials 13 are embedded in the Ni-Sn conductive layer 12. The core materials 13 are arranged on the inner side of the protrusions 11a and 12a. The Ni-Sn conductive layer 12 covers the plurality of core materials 13. Due to the plurality of core materials 13, the outer surface of the Ni-Sn conductive layer 12 is raised to form the protrusions 11a and 12a.

[0062] The conductive particles 11 have an insulating substance 14 disposed on the outer surface of the Ni-Sn conductive layer 12. At least a portion of the outer surface of the Ni-Sn conductive layer 12 is coated with the insulating substance 14. The insulating substance 14 is formed of an insulating material and is an insulating particle. In this way, the conductive particles of the present invention may have an insulating substance disposed on the outer surface of the Ni-Sn conductive layer. However, the conductive particles of the present invention may not necessarily have an insulating substance.

[0063] In the conductive particles 11, the average tin content in the entire region of the Ni-Sn conductive layer 12 is less than 5% by weight. In the conductive particles 11, when the tin content in the thickness direction of the Ni-Sn conductive layer 12 is measured by TEM-EDX, the maximum value of the tin content in the region of 1 / 2 thickness outside the Ni-Sn conductive layer 12 is 5% by weight or more.

[0064] Figure 3 It is a cross-sectional view which shows the electroconductive particle which concerns on 3rd Embodiment of this invention.

[0065] Figure 3 The conductive particle 21 shown has a substrate particle 2, a Ni—Sn conductive layer 22A (first conductive layer), a plurality of core materials 13, and a plurality of insulating materials 14. The conductive particle 21 has a Ni—Sn conductive layer 22A (first conductive layer) on the side opposite to the substrate particle 2 side, and has a second conductive layer 22B on the substrate particle 2 side.

[0066] Only the second conductive layer 22B is different between the conductive particles 11 and 21. That is, a conductive layer having a single-layer structure is formed in the conductive particles 11, while a conductive layer having a two-layer structure is formed in the conductive particles 21. The Ni—Sn conductive layer 12 is formed in the conductive particles 11, while the Ni—Sn conductive layer 22A (first conductive layer) and the second conductive layer 22B are formed in the conductive particles 21. In the conductive particles 21, the Ni—Sn conductive layer 22A (first conductive layer) and the second conductive layer 22B are formed as different conductive layers.

[0067] The second conductive layer 22B is arranged on the surface of the substrate particle 2. The second conductive layer 22B is arranged between the substrate particle 2 and the Ni-Sn conductive layer 22A (the first conductive layer). The second conductive layer 22B is in contact with the substrate particle 2. The Ni-Sn conductive layer 22A (the first conductive layer) is in contact with the second conductive layer 22B. Therefore, the second conductive layer 22B is arranged on the surface of the substrate particle 2, and the Ni-Sn conductive layer 22A (the first conductive layer) is arranged on the surface of the second conductive layer 22B. The conductive particle 21 has a plurality of protrusions 21a on the surface. The Ni-Sn conductive layer 22A (the first conductive layer) has a plurality of protrusions 22Aa on the outer surface. The second conductive layer 22B has a plurality of protrusions 22Ba on the outer surface.

[0068] In the conductive particles 21, the average tin content in the entire region of the Ni-Sn conductive layer 22A is less than 5% by weight. In the conductive particles 21, when the tin content in the thickness direction of the Ni-Sn conductive layer 22A is measured by TEM-EDX, the maximum value of the tin content in the region of 1 / 2 thickness outside the Ni-Sn conductive layer 22A is 5% by weight or more.

[0069] Hereinafter, the substrate particles and the Ni—Sn conductive layer will be described in detail.

[0070] (Base material particles)

[0071] The material of the substrate particles is not particularly limited. The material of the substrate particles may be an organic material or an inorganic material. As substrate particles formed only by the organic material, resin particles and the like may be cited. As substrate particles formed only by the inorganic material, inorganic particles other than metals and the like may be cited. As substrate particles formed by both the organic material and the inorganic material, organic-inorganic hybrid particles and the like may be cited. From the viewpoint of further improving the compression characteristics of the substrate particles, the substrate particles are preferably resin particles or organic-inorganic hybrid particles, and more preferably resin particles.

[0072] As the organic material, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene can be cited; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenolic resin, melamine resin, benzoguanamine resin, urea formaldehyde resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene ether, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, and divinylbenzene polymers can be cited. The divinylbenzene polymer can be a divinylbenzene copolymer. As the divinylbenzene copolymer, divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylate copolymer can be cited. From the viewpoint that the compression characteristics of the substrate particles can be easily controlled within a suitable range, the material of the substrate particles is preferably a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group.

[0073] When the substrate particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, examples of the polymerizable monomer having an ethylenically unsaturated group include non-crosslinking monomers and crosslinking monomers.

[0074] Examples of the non-crosslinking monomers include: vinyl compounds, such as styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; vinyl acetate compounds, vinyl butyrate compounds, vinyl laurate compounds, and vinyl stearate compounds; halogen-containing monomers such as vinyl chloride and vinyl fluoride; (meth)acrylic acid compounds, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, and propylene (meth)acrylate. (Meth)acrylate alkyl ester compounds such as stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylate compounds containing oxygen atoms such as 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; (meth)acrylate compounds containing halogens such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; as α-olefin compounds, olefin compounds such as diisobutylene, isobutylene, linear α-olefins, ethylene, and propylene can be mentioned; as conjugated diene compounds, isoprene, butadiene, etc. can be mentioned.

[0075] Examples of the crosslinking monomer include: vinyl compounds such as divinylbenzene, 1,4-divinyloxybutane, and divinyl sulfone; (meth)acrylic compounds such as tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. ) acrylate, polytetramethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate and other multifunctional (meth)acrylate compounds; as the allyl compound, there can be mentioned triallyl (iso)cyanurate, triallyl trimellitic acid, diallyl phthalate, diallyl acrylamide, diallyl ether; as the silane compound, there can be mentioned tetramethoxysilane, tetraethoxysilane, methyl trimethoxysilane, methyl triethoxysilane, ethyl trimethoxysilane, ethyl triethoxysilane, isopropyl trimethoxysilane, isobutyl trimethoxysilane, cyclohexyl trimethoxysilane, n-hexyl trimethoxysilane, n-octyl triethoxysilane, n-decyl trimethoxysilane, silanealkoxide compounds such as trimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, and diphenyldimethoxysilane; vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyldimethoxysilane Silane alcohol salts containing polymerizable double bonds such as methoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-phenylvinyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as single-terminated modified silicone oil, double-terminated silicone oil, and side-chain silicone oil; carboxyl-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride, etc.

[0076] The substrate particles can be obtained by polymerizing the polymerizable monomer with the ethylenically unsaturated group. It is not particularly limited as the polymerization method, and known methods such as free radical polymerization, ionic polymerization, polycondensation (condensation polymerization, polycondensation), addition condensation, living polymerization and living free radical polymerization can be cited. In addition, as other polymerization methods, suspension polymerization in the presence of a free radical polymerization initiator can be cited.

[0077] Examples of the inorganic material include silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, carbon black, silicate glass, borosilicate glass, lead glass, soda-lime glass, and alumina silicate glass.

[0078] The substrate particles may be organic-inorganic hybrid particles. The substrate particles may be core-shell particles. When the substrate particles are organic-inorganic hybrid particles, the inorganic material of the substrate particles may include silica, alumina, barium titanate, zirconium oxide, and carbon black. The inorganic material is preferably not a metal. The substrate particles formed by the silica are not particularly limited, and may include substrate particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form crosslinked polymer particles and then firing as needed. As the organic-inorganic hybrid particles, organic-inorganic hybrid particles formed by crosslinking an alkoxysilyl polymer and an acrylic resin may be included.

[0079] The organic-inorganic hybrid particles are preferably core-shell organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. The substrate particles are preferably organic-inorganic hybrid particles having an organic core and an inorganic shell disposed on the surface of the organic core.

[0080] Examples of the material of the organic core include the above-mentioned organic materials.

[0081] As the material of the inorganic shell, the inorganic substances exemplified as the material of the substrate particles can be cited. The material of the inorganic shell is preferably silicon dioxide. The inorganic shell is preferably formed by forming a shell-like object by a sol-gel method on the surface of the core with a metal alkoxide and then firing the shell-like object. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed by a silane alkoxide.

[0082] The particle size of the substrate particles is preferably 0.1 μm or more, more preferably 1 μm or more. The particle size of the substrate particles is preferably 1000 μm or less, more preferably 500 μm or less, further preferably 100 μm or less, particularly preferably 30 μm or less, and most preferably 10 μm or less. When the particle size of the substrate particles is above the lower limit, the contact area between the conductive particles and the electrodes increases, thereby improving the conduction reliability between the electrodes, and further reducing the connection resistance between the electrodes connected by the conductive particles. In addition, when a conductive portion is formed on the surface of the substrate particles by electroless plating, it is not easy to form condensed conductive particles. When the particle size of the substrate particles is below the upper limit, it is easy to fully compress the conductive particles, which can further reduce the connection resistance between the electrodes, and further reduce the interval between the electrodes.

[0083] The particle size of the substrate particles means the diameter when the substrate particles are spherical, and means the diameter when the substrate particles are in a shape other than a spherical shape, assuming a sphere having a volume equivalent to the substrate particles.

[0084] The particle size of the substrate particles represents the number average particle size. With regard to the particle size of the substrate particles, 50 arbitrary substrate particles are observed under an electron microscope or an optical microscope, and the average value of the particle size of each substrate particle is calculated, or a particle size distribution measuring device is used to obtain it. In the observation under an electron microscope or an optical microscope, the particle size of each substrate particle is obtained as the particle size under the circle equivalent diameter. In the observation under an electron microscope or an optical microscope, the average particle size under the circle equivalent diameter of any 50 substrate particles is roughly equal to the average particle size under the sphere equivalent diameter. In the particle size distribution measuring device, the particle size of each substrate particle is obtained as the particle size under the sphere equivalent diameter. The average particle size of the substrate particles is preferably calculated using a particle size distribution measuring device.

[0085] In the conductive particles, when the particle size of the substrate particles is measured, for example, it can be measured as follows. Add to "TECHNOVIT4000" manufactured by Kulzer Company in such a manner that the content of the conductive particles is 30% by weight, and disperse to prepare an embedded resin body for conductive particle inspection. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles in a manner near the center of the substrate particles of the conductive particles dispersed in the embedded resin body for inspection. In addition, using a field emission scanning electron microscope (FE-SEM), the image magnification is set to 25,000 times, 50 conductive particles are randomly selected, and the substrate particles of each conductive particle are observed. The particle size of the substrate particles in each conductive particle is measured, and the arithmetic average is taken as the particle size of the substrate particles.

[0086] (Ni-Sn conductive layer)

[0087] The conductive particles include a Ni-Sn conductive layer including nickel and tin. In the conductive particles, the average content of tin in the entire region of the Ni-Sn conductive layer is less than 5% by weight. In the conductive particles, when the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the content of tin in the region (R1) of 1 / 2 of the thickness outside the Ni-Sn conductive layer is 5% by weight or more. The region R1 is a region of 50% of the thickness outside the Ni-Sn conductive layer.

[0088] Figure 4 It is a schematic diagram for demonstrating each area|region of the Ni-Sn conductive layer in the conductive particle which concerns on 1st Embodiment of this invention. Figure 4 It is a schematic diagram for explaining each region of the Ni—Sn conductive layer 3 in the conductive particle 1 .

[0089] The region (R1) of 1 / 2 thickness of the outer side of the Ni-Sn conductive layer is a region extending from the outer surface of the Ni-Sn conductive layer to 1 / 2 thickness of the Ni-Sn conductive layer in the inner direction. Figure 4 In FIG. 1 , it is a region outside the dotted line L1 of the Ni—Sn conductive layer 3. The region R1 is an outer surface portion of the Ni—Sn conductive layer 3. The region R1 is a region different from a region of the Ni—Sn conductive layer 3 on the substrate particle 2 side.

[0090] The region (R2) of 1 / 2 thickness of the inner side of the Ni-Sn conductive layer is a region extending from the inner surface of the Ni-Sn conductive layer to 1 / 2 thickness of the Ni-Sn conductive layer in the outer direction. Figure 4 In FIG. 1 , it is a region on the inner side of the dotted line L1 of the Ni—Sn conductive layer 3. The region R2 is a region on the substrate particle 2 side of the Ni—Sn conductive layer 3. The region R2 is a region different from the outer surface portion of the Ni—Sn conductive layer 3.

[0091] In the conductive particles, the average content of tin in the overall region of the Ni-Sn conductive layer is less than 5% by weight. In the conductive particles, due to the composition, the initial resistance can be reduced. From the viewpoint of further reducing the initial resistance, the average content of tin in the overall region of the Ni-Sn conductive layer is preferably 4.5% by weight or less, more preferably 4.0% by weight or less, and more preferably 3.5% by weight or less. From the viewpoint of further reducing the connection resistance after exposure to the presence of acid, the average content of tin in the overall region of the Ni-Sn conductive layer exceeds 0% by weight, preferably 0.1% by weight or more, and more preferably 0.5% by weight or more.

[0092] The Ni—Sn layer preferably contains nickel as a main metal. The average nickel content in the entire region of the Ni—Sn conductive layer is preferably 50 wt % or more, more preferably 80 wt % or more, and preferably 99.9 wt % or less, more preferably 99.5 wt % or less.

[0093] The average contents of nickel and tin in the entire region of the Ni—Sn conductive layer can be measured by ICP-MS method or the like.

[0094] In the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the tin content in the region (R1) of 1 / 2 thickness outside the Ni-Sn conductive layer is 5 wt % or more. In the conductive particles, due to the above structure, even when exposed to high voltage for a long time in a high temperature and high humidity environment, the movement of charges in the Ni-Sn conductive layer can be prevented.

[0095] In the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the tin content of the Ni-Sn conductive layer is preferably present in the region R1. In the conductive particles, the maximum value of the tin content in the entire region of the Ni-Sn conductive layer is preferably present in the region R1. In the conductive particles, the region where the maximum value of the tin content in the entire region of the Ni-Sn conductive layer exists is preferably the region R1. In the conductive particles, the tin content is preferably the maximum value in the region R1. In the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the tin content in the region R1 is preferably greater than the maximum value of the tin content in the region R2. In the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the maximum value of the tin content of the Ni-Sn conductive layer is preferably the maximum value of the tin content in the region R1.

[0096] In the conductive particles, tin is unevenly distributed in the thickness direction of the Ni—Sn conductive layer. In the conductive particles, tin is unevenly distributed in the thickness direction of the Ni—Sn conductive layer.

[0097] In the conductive particles, in the Ni-Sn conductive layer, the tin content of the region R1 is preferably different in a manner that the tin content of the region R2 is greater than that of the region R1, and the tin content preferably has a gradient. In the Ni-Sn conductive layer, the tin is preferably unevenly distributed in a manner that the tin is more present in the region R1 than in the region R2. In the Ni-Sn conductive layer, the average tin content in the region R1 is preferably greater than the average tin content in the region R2. Due to the presence of such a concentration difference and a concentration gradient, the connection resistance after exposure to the presence of an acid can be further reduced, and the conductive particles are exposed to a high voltage for a long time under a high temperature and high humidity environment, which can further effectively prevent the movement of charges in the Ni-Sn conductive layer.

[0098] From the viewpoint of further effectively exerting the effects of the present invention, the average tin content in the region R1 is preferably 0.5 wt% or more, more preferably 1.0 wt% or more, further preferably 3.0 wt% or more, and is preferably 10 wt% or less, more preferably 9.0 wt% or less, further preferably 8.0 wt% or less, based on 100 wt% of the region R1 as a whole.

[0099] From the viewpoint of further effectively exerting the effect of the present invention, the average content of tin in the region R2 is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably 3% by weight or less in the entire 100% by weight of the region R2. The lower limit of the average content of tin in the region R2 in the entire 100% by weight of the region R2 is not particularly limited. The average content of tin in the region R2 in the entire 100% by weight of the region R2 may be 3% by weight or more.

[0100] In the conductive particles of the present invention, it is very important to control the distribution of tin contained in the Ni—Sn conductive layer in the thickness direction.

[0101] When the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, the content of tin in the region R1 is preferably 65% ​​by weight or more, more preferably 70% by weight or more, and further preferably 80% by weight or more, of the total 100% by weight of tin contained in the entire Ni-Sn conductive layer. From the viewpoint of further effectively exerting the effect of the present invention, when the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, in the region (R1) of 1 / 2 of the thickness of the outer side of the Ni-Sn conductive layer, it is preferred that 80% by weight or more of the total 100% by weight of tin contained in the entire Ni-Sn conductive layer be included. Of the total 100% by weight of tin contained in the entire Ni-Sn conductive layer, the content of tin in the region R1 is further preferably 85% by weight or more, further preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably 100% by weight (total amount). When the tin content in the region R1 is above the lower limit out of a total of 100 weight % of tin contained in the entire Ni—Sn conductive layer, the connection resistance after exposure to the presence of acid can be further reduced, and the movement of charges in the Ni—Sn conductive layer can be further effectively prevented even when the conductive particles are exposed to high voltage for a long time in a high temperature and high humidity environment.

[0102] From the viewpoint of further effectively exerting the effect of the present invention, in the conductive particles, the ratio of the region containing tin in the thickness 100% of the Ni-Sn conductive layer is preferably 5% or more, more preferably 15% or more, and preferably 95% or less, more preferably 80% or less, and more preferably 50% or less. From the viewpoint of further effectively exerting the effect of the present invention, in the conductive particles, when the content of tin in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, it is preferred that tin is contained in the region of 15% or more of the thickness of the Ni-Sn conductive layer. In the conventional conductive particles, when the content of tin in the thickness direction of the conductive layer is measured by TEM-EDX, the ratio of the region containing tin in the thickness 100% of the conductive layer is about 10%. In the conductive particles of the present invention, when the ratio of the region containing tin in the thickness 100% of the Ni-Sn conductive layer is above the lower limit and below the upper limit, the connection resistance after exposure to the presence of acid can be further reduced, and even if the conductive particles are exposed to high voltage for a long time under high temperature and high humidity, the movement of charges in the Ni-Sn conductive layer can be further effectively prevented.

[0103] In the conductive particles of the present invention, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, it is very important to control the relationship between the thickness of the region containing tin (peak width in the distribution curve) and the maximum value of the tin content in the region (peak height in the distribution curve). That is, in the conductive particles, in the distribution curve of the tin content measured by TEM-EDX, when the horizontal axis is set to the distance in the thickness direction from the outer surface when the thickness of the Ni-Sn conductive layer is 100% (%), and the vertical axis is set to the tin content (weight %), it is very important to control the peak width and peak height of the distribution curve.

[0104] The shape of the distribution curve of the tin content may be a mountain shape or a part of a mountain shape. The distribution curve of the tin content may be unimodal or multimodal. The distribution curve of the tin content may have one peak or multiple peaks. In the case where the distribution curve of the tin content has multiple peaks, the proportion of the area containing tin in the thickness of 100% of the Ni-Sn conductive layer is the sum of the widths of each peak. It should be noted that the distribution curve of the tin content preferably has one peak, and as described above, the peak (the maximum value of the tin content of the Ni-Sn conductive layer) is preferably present in the region R1, and more preferably present on the outermost surface of the Ni-Sn conductive layer.

[0105] In the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, tin can be distributed in a wider area in the thickness direction of the Ni-Sn conductive layer, and the maximum value of the tin content of the Ni-Sn conductive layer is small. In the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, tin can be distributed in a wider area in the thickness direction of the Ni-Sn conductive layer, and the maximum value of the tin content in the region (R1) of 1 / 2 of the thickness on the outside of the Ni-Sn conductive layer is small. In addition, in the conductive particles, when the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, tin can be distributed in a narrower area in the thickness direction of the Ni-Sn conductive layer, and the maximum value of the tin content is large. When the tin content in the thickness direction of the Ni-Sn conductive layer in the conductive particles is measured by TEM-EDX, it can be found that tin is distributed in a narrower area in the thickness direction of the Ni-Sn conductive layer, and the maximum tin content is larger in the area (R1) of 1 / 2 of the thickness on the outside of the Ni-Sn conductive layer.

[0106] Tin is distributed in a wider area in the thickness direction of the Ni-Sn conductive layer, and when the maximum value of the tin content of the Ni-Sn conductive layer (the maximum value of the tin content in the region R1) is small, the proportion of the area containing tin in the thickness 100% of the Ni-Sn conductive layer is particularly preferably 20% or more, and most preferably 25% or more. In addition, in the case, the proportion of the area containing tin in the thickness 100% of the Ni-Sn conductive layer is particularly preferably 50% or less, and most preferably 40% or less. In the case, the tin content in the thickness direction of the Ni-Sn conductive layer is determined by TEM-EDX. In the determination, in the area where the thickness of the Ni-Sn conductive layer is more than 10% and less than 50%, tin is preferably contained in an amount of more than 5% by weight. In the determination, in the thickness 100% of the Ni-Sn conductive layer, the area where the tin content is more than 5% by weight is preferably 8% or more, more preferably 10% or more, and further preferably 12.5% ​​or more, and preferably less than 50%, more preferably less than 40%, and further preferably less than 30%. In addition, in the case, the tin content in the thickness direction of the Ni-Sn conductive layer is determined by TEM-EDX. In the measurement, in the region (R1) of 1 / 2 thickness on the outside of the Ni-Sn conductive layer, the maximum value of the tin content is 5% by weight or more, preferably 7% by weight or more, more preferably 10% by weight or more, and preferably 50% by weight or less, more preferably 40% by weight or less, further preferably 30% by weight or less, and particularly preferably 20% by weight or less. It should be noted that in the measurement, it is more preferred that the Ni-Sn conductive layer contains tin at a content of 5% by weight or more in a region of 10% or more and less than 50%% of the thickness, and in the region (R1) of 1 / 2 thickness on the outside of the Ni-Sn conductive layer, the maximum value of the tin content is 5% by weight or more and 40% by weight or less.

[0107] Tin is distributed in a narrower area in the thickness direction of the Ni-Sn conductive layer, and when the maximum value of the tin content of the Ni-Sn conductive layer (the maximum value of the tin content in the region R1) is large, the proportion of the area containing tin in the thickness 100% of the Ni-Sn conductive layer is particularly preferably 5% or more, and most preferably 10% or more. In addition, in the case, the proportion of the area containing tin in the thickness 100% of the Ni-Sn conductive layer is further preferably 40% or less, particularly preferably 30% or less, and most preferably 25% or less. In the case, the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX. In the measurement, in the area below 30% of the thickness of the Ni-Sn conductive layer, tin is preferably contained in an amount of 5 weight % or more. In the determination, in the thickness 100% of the Ni-Sn conductive layer, the area where the tin content is 5% by weight or more is preferably 0.1% or more, more preferably 0.5% or more, further preferably 1.0% or more, and preferably 30% or less, more preferably 25% or less, further preferably 20% or less, and most preferably 10% or less. In addition, in the case, the tin content in the thickness direction of the Ni-Sn conductive layer is determined by TEM-EDX. In the determination, in the area (R1) of 1 / 2 of the thickness of the outside of the Ni-Sn conductive layer, the maximum value of the tin content is 5% by weight or more, preferably 10% or more, and more preferably 15% or more. In addition, in the determination, in the area (R1) of 1 / 2 of the thickness of the outside of the Ni-Sn conductive layer, the maximum value of the tin content is preferably 95% by weight or less, more preferably 90% by weight or less, further preferably 80% by weight or less, particularly preferably 50% by weight or less, and most preferably 40% by weight or less. It should be noted that in the above-mentioned measurement, it is more preferred that the tin content in the region below 30% of the thickness of the Ni-Sn conductive layer is greater than 5 weight %, and that the maximum tin content in the region (R1) of 1 / 2 of the thickness on the outside of the Ni-Sn conductive layer is greater than 10 weight %.

[0108] The average content of nickel and tin in the region R1, the average content of nickel and tin in the region R2, the maximum value of the content of tin in the region R1, and the maximum value of the content of tin in the region R2 can be measured by TEM-EDX. Specifically, a focused ion beam is used to prepare a thin film slice of the conductive particles. Then, a transmission electron microscope FE-TEM ("JEM-2010FEF" manufactured by JEOL Ltd.) is used to measure the contents of nickel and tin in the thickness direction of the Ni-Sn conductive layer by an energy dispersive X-ray analyzer (EDS). It should be noted that in the obtained gravimetric analysis diagram, among the inflection points on the curve representing the content of all metals contained in the Ni-Sn conductive layer, the outermost inflection point is used as the starting point (thickness 0%) of the thickness direction of the Ni-Sn conductive layer, and the innermost inflection point is used as the end point (thickness 100%) of the thickness direction of the Ni-Sn conductive layer.

[0109] The Ni-Sn conductive layer may include nickel, tin, or metals other than nickel and tin. Examples of the metals other than nickel and tin include silver, copper, platinum, zinc, iron, lead, aluminum, cobalt, indium, palladium, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and tin-doped indium oxide (ITO). These metals may be used alone or in combination of two or more.

[0110] The average content of the metals other than nickel and tin in the overall region of the Ni-Sn conductive layer is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably 3% by weight or less. The lower limit of the average content of the metals other than nickel and tin in the overall region of the Ni-Sn conductive layer is not particularly limited. The average content of the metals other than nickel and tin in the overall region of the Ni-Sn conductive layer may be 0.01% by weight or more, and may be 0.1% by weight or more.

[0111] It should be noted that when the Ni—Sn conductive layer includes metal other than nickel and tin, the average nickel content and the average tin content in the region R1 and the region R2 are calculated by taking the total of the nickel content and the tin content as 100 weight %.

[0112] The thickness of the Ni-Sn conductive layer is preferably 5 nm or more, more preferably 10 nm or more, further preferably 80 nm or more, and preferably 500 nm or less, more preferably 300 nm or less. When the thickness of the Ni-Sn conductive layer is above the lower limit and below the upper limit, the connection resistance can be further reduced. The thickness of the Ni-Sn conductive layer represents the average thickness of the Ni-Sn conductive layer in the conductive particles.

[0113] The method for forming the Ni-Sn conductive layer is not particularly limited. As the method for forming the Ni-Sn conductive layer, for example, a method based on electroless plating, a method based on electroplating, a method based on physical vapor deposition, and a method of applying a metal powder or a paste containing a metal powder and an adhesive to the surface of the particle can be cited. In particular, the formation of the Ni-Sn conductive layer is simple, so a method based on electroless plating is preferred. As the method based on physical vapor deposition, methods such as vacuum evaporation, ion plating and ion sputtering can be cited.

[0114] Examples of methods for controlling the content and distribution of nickel and tin in the Ni—Sn conductive layer include adjusting the concentrations of tin and a complexing agent in a plating solution and adjusting the pH of a reaction solution in electroless plating.

[0115] The conductive particles may include a plurality of conductive layers. The conductive particles may include a conductive layer (another conductive layer) other than the Ni—Sn conductive layer. When the conductive particles include a plurality of conductive layers, the Ni—Sn conductive layer is preferably the outermost layer of the conductive particles. When the conductive particles include a plurality of conductive layers, the Ni—Sn conductive layer is preferably the outermost conductive layer.

[0116] The structure of the conductive layer other than the Ni—Sn conductive layer is not particularly limited. The material of the conductive layer other than the Ni—Sn conductive layer may be the same as or different from the material of the Ni—Sn conductive layer.

[0117] The conductive particles of the present invention preferably have protrusions on the surface. The Ni-Sn conductive layer preferably has protrusions on the outer surface. An oxide film is mostly formed on the surface of the electrode connected by the conductive particles. By using conductive particles with conductive protrusions, after the conductive particles are arranged between the electrodes, the oxide film is effectively removed by pressing. Therefore, the electrode and the conductive particles can be further reliably contacted, and the connection resistance between the electrodes can be further reduced. In addition, when the conductive particles have an insulating substance on the surface or the conductive particles are dispersed in a resin and used as a conductive material, the insulating substance or resin between the conductive particles and the electrode can be effectively removed by the protrusions of the conductive particles. Therefore, the conduction reliability between the electrodes can be improved.

[0118] The protrusions are preferably multiple. The protrusions on the outer surface of the conductive layer of each of the conductive particles are preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The number of the protrusions is preferably 1000 or less, more preferably 800 or less. The upper limit of the number of protrusions can be appropriately selected according to the particle size of the conductive particles, etc.

[0119] The average height of the plurality of protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, and preferably 0.9 μm or less, more preferably 0.2 μm or less. When the average height of the protrusions is above the lower limit and below the upper limit, the connection resistance between the electrodes is effectively reduced. The average height of the protrusions can be calculated by the following method. 50 conductive particles of the present invention are observed under an electron microscope or an optical microscope, and the heights of all protrusions on the peripheral edge portions of the observed conductive particles are measured. The height of the convex portion is measured using the surface without protrusions as the reference surface, and the average value is calculated.

[0120] From the viewpoint of further effectively exerting the effect of the present invention, the surface area of ​​the portion having the protrusion is preferably 10% or more, more preferably 20% or more, and further preferably 30% or more of the total surface area of ​​the outer surface of the Ni-Sn conductive layer 100%. The upper limit of the proportion of the surface area of ​​the portion having the protrusion in the total surface area of ​​the outer surface of the Ni-Sn conductive layer 100% is not particularly limited, and is usually 100% or less, preferably 99% or less.

[0121] The ratio of the surface area of ​​the portion having the protrusions can be calculated by the following method: 50 conductive particles of the present invention are observed under an electron microscope or an optical microscope, the ratio of the area of ​​the portion where the protrusions appear on the orthographic projection plane is measured, and the average value is calculated.

[0122] (Core material)

[0123] By embedding the core material in the Ni-Sn conductive layer, it is easy to make the Ni-Sn conductive layer have multiple protrusions on the outer surface. However, in order to form protrusions on the outer surface of the conductive particles and the Ni-Sn conductive layer, it is not necessary to use a core material, and it is preferred not to use a core material. The conductive particles preferably do not have a core material for making the outer surface of the Ni-Sn conductive part bulge inside and inside the Ni-Sn conductive layer. The Ni-Sn conductive layer preferably does not include a core material for making the outer surface of the Ni-Sn conductive layer bulge inside and inside the Ni-Sn conductive layer.

[0124] As a method for forming the protrusion, there can be cited a method of attaching a core material to the surface of a substrate particle and then forming a Ni-Sn conductive layer by electroless plating; and a method of attaching a core material after forming a Ni-Sn conductive layer by electroless plating on the surface of a substrate particle, and further forming a Ni-Sn conductive layer by electroless plating, etc. As another method for forming the protrusion, there can be cited a method of adding a core material in the middle stage of forming a Ni-Sn conductive layer on the surface of a substrate particle, etc.

[0125] As a method for configuring the core material on the surface of the substrate particles, for example, a method of adding the core material to the dispersion of the substrate particles, causing the core material to aggregate and adhere to the surface of the substrate particles through, for example, van der Waals forces; and a method of adding the core material to a container containing the substrate particles, causing the core material to adhere to the surface of the substrate particles based on mechanical effects such as the rotation of the container, etc. In particular, in order to easily control the amount of the attached core material, a method of aggregating and adhering the core material to the surface of the substrate particles in the dispersion is preferred.

[0126] As the material constituting the core material, conductive materials and non-conductive materials can be cited. As the conductive material, for example, conductive non-metals such as metals, metal oxides, graphite, and conductive polymers can be cited. As the conductive polymer, polyacetylene can be cited. As the non-conductive material, silicon dioxide, aluminum oxide, barium titanate, and zirconium oxide can be cited. In particular, from the aspect of being able to improve conductivity and further effectively reduce connection resistance, metals are preferred. The core material is preferably metal particles.

[0127] As the metal, for example, metals such as gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium and cadmium, and alloys composed of two or more metals such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy and tungsten carbide, etc. can be cited. Among them, nickel, copper, silver or gold is preferred. The metal used to form the core material may be the same as or different from the metal used to form the conductive layer. The metal used to form the core material preferably includes the metal used to form the conductive layer. The metal used to form the core material preferably includes nickel.

[0128] Specific examples of the material of the core substance include barium titanate (Mohs hardness 4.5), nickel (Mohs hardness 5), silicon dioxide (Mohs hardness 6~7), titanium oxide (Mohs hardness 7), zirconium oxide (Mohs hardness 8~9), aluminum oxide (Mohs hardness 9), tungsten carbide (Mohs hardness 9) and diamond (Mohs hardness 10). The inorganic particles are preferably nickel, silicon dioxide, titanium oxide, zirconium oxide, aluminum oxide, tungsten carbide or diamond, and more preferably silicon dioxide, titanium oxide, zirconium oxide, aluminum oxide, tungsten carbide or diamond. The inorganic particles are further preferably titanium oxide, zirconium oxide, aluminum oxide, tungsten carbide or diamond, and particularly preferably zirconium oxide, aluminum oxide, tungsten carbide or diamond. The Mohs hardness of the material of the core substance is preferably 5 or more, more preferably 6 or more, further preferably 7 or more, and particularly preferably 7.5 or more.

[0129] The shape of the core material is not particularly limited. The shape of the core material is preferably a block. Examples of the core material include a particle-shaped block, an aggregated block formed by agglomeration of a plurality of fine particles, and an indefinite-shaped block.

[0130] The average diameter (average particle size) of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, and preferably 0.9 μm or less, more preferably 0.2 μm or less. When the average diameter of the core material is above the lower limit and below the upper limit, the connection resistance between electrodes is effectively reduced.

[0131] The “average diameter (average particle size)” of the core material refers to the number average diameter (number average particle size). The average diameter of the core material can be obtained by, for example, observing 50 arbitrary core materials under an electron microscope or an optical microscope and calculating the average value.

[0132] (Insulating material)

[0133] The conductive particles of the present invention preferably have an insulating substance disposed on the outer surface of the Ni-Sn conductive layer. In this case, when the conductive particles are used for connection between electrodes, short circuits between adjacent electrodes can be prevented. Specifically, when a plurality of conductive particles are in contact, an insulating substance is present between the plurality of electrodes, so that short circuits between electrodes adjacent to each other in the transverse direction rather than between upper and lower electrodes can be prevented. It should be noted that, when connecting between electrodes, the insulating substance between the Ni-Sn conductive layer of the conductive particles and the electrodes can be easily excluded by pressurizing the conductive particles at the two electrodes. When the conductive particles have a plurality of protrusions on the outer surface of the Ni-Sn conductive layer, the insulating substance between the Ni-Sn conductive layer of the conductive particles and the electrodes can be easily excluded.

[0134] The insulating substance is preferably insulating particles because the insulating substance can be more easily removed during compression bonding between electrodes.

[0135] Specific examples of the insulating resin as a material of the insulating substance include polyolefins, (meth)acrylate polymers, (meth)acrylate copolymers, block polymers, thermoplastic resins, crosslinked products of thermoplastic resins, thermosetting resins, and water-soluble resins.

[0136] As the polyolefins, polyethylene, ethylene-vinyl acetate copolymer and ethylene-acrylate copolymer etc. can be cited. As the (meth)acrylate polymer, polymethyl (meth)acrylate, polyethyl (meth)acrylate and polybutyl (meth)acrylate etc. can be cited. As the block polymer, polystyrene, styrene-acrylate copolymer, SB type styrene-butadiene block copolymer and SBS type styrene-butadiene block copolymer and hydrogenated products thereof etc. can be cited. As the thermoplastic resin, vinyl polymer and vinyl copolymer etc. can be cited. As the thermosetting resin, epoxy resin, phenolic resin and melamine resin etc. can be cited. As the water-soluble resin, polyvinyl alcohol, polyacrylic acid, polyacrylamide, polyvinyl pyrrolidone, polyethylene oxide and methylcellulose etc. can be cited. The insulating resin preferably comprises a water-soluble resin, more preferably comprises polyvinyl alcohol.

[0137] As the method for configuring the insulating material on the surface of the Ni-Sn conductive layer, chemical methods and physical or mechanical methods etc. can be cited. As the chemical method, for example, interfacial polymerization, suspension polymerization in the presence of particles and emulsion polymerization etc. can be cited. As the physical or mechanical method, methods based on spray drying, hybridization, electrostatic adhesion, spraying, dipping and vacuum evaporation etc. can be cited. In particular, from the aspect that the insulating material is not easy to detach, it is preferred to configure the insulating material on the surface of the conductive layer by chemical bonding.

[0138] The outer surface of the Ni-Sn conductive layer and the surface of the insulating particles may be coated with a compound having a reactive functional group, respectively. The outer surface of the conductive layer and the surface of the insulating particles may not be directly chemically bonded, but may be indirectly chemically bonded through a compound having a reactive functional group. After a carboxyl group is introduced into the outer surface of the conductive layer, the carboxyl group may be chemically bonded to the functional group on the surface of the insulating particles through a polymer electrolyte such as polyethyleneimine.

[0139] The average diameter (average particle size) of the insulating substance can be appropriately selected according to the particle size of the conductive particles and the purpose of the conductive particles. The average diameter (average particle size) of the insulating substance is preferably greater than 0.005 μm, more preferably greater than 0.01 μm, and preferably less than 1 μm, more preferably less than 0.5 μm. When the average diameter of the insulating substance is greater than the lower limit, when the conductive particles are dispersed in the binder resin, the conductive layers in the plurality of conductive particles are not easily in contact with each other. When the average diameter of the insulating particles is less than the upper limit, when connecting between electrodes, in order to exclude the insulating substance between the electrode and the conductive particles, it is not necessary to make the pressure too high or to heat to a high temperature.

[0140] The “average diameter (average particle size)” of the insulating substance refers to the number average diameter (number average particle size). The average diameter of the insulating substance can be determined using a particle size distribution measuring device or the like.

[0141] (Conductive materials)

[0142] The conductive material of the present invention comprises the conductive particles and a binder resin. The conductive particles are preferably dispersed in a binder resin and used, and are preferably dispersed in a binder resin and used as a conductive material. The conductive material is preferably an anisotropic conductive material. The conductive material is preferably used for electrical connection between electrodes. The conductive material is preferably a circuit connection material.

[0143] The binder resin is not particularly limited, and a known insulating resin is used as the binder resin.

[0144] Examples of the binder resin include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, and elastomers. The binder resin may be used alone or in combination of two or more.

[0145] As the vinyl resin, for example, vinyl acetate resin, acrylic resin and styrene resin can be cited. As the thermoplastic resin, for example, polyolefin resin, ethylene-vinyl acetate copolymer and polyamide resin can be cited. As the curable resin, for example, epoxy resin, polyurethane resin, polyimide resin and unsaturated polyester resin can be cited. It should be noted that the curable resin can be a room temperature curing resin, a heat curing resin, a light curing resin or a moisture curing resin. The curable resin can be used in combination with a curing agent. As the thermoplastic block copolymer, for example, styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-butadiene-styrene block copolymer hydrogenated product and styrene-isoprene-styrene block copolymer hydrogenated product can be cited. As the elastomer, for example, styrene-butadiene copolymer rubber and acrylonitrile-styrene block copolymer rubber can be cited.

[0146] The conductive material may contain various additives such as fillers, extenders, softeners, plasticizers, polymerization catalysts, curing catalysts, colorants, antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents, and flame retardants in addition to the conductive particles and the binder resin.

[0147] The conductive material of the present invention can be used as a conductive paste and a conductive film. When the conductive material of the present invention is a conductive film, a film not containing conductive particles can be laminated on the conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.

[0148] In 100 wt % of the conductive material, the content of the binder resin is preferably 10 wt % or more, more preferably 30 wt % or more, further preferably 50 wt % or more, particularly preferably 70 wt % or more, and preferably 99.99 wt % or less, more preferably 99.9 wt % or less. When the content of the binder resin is above the lower limit and below the upper limit, conductive particles can be efficiently arranged between electrodes, further improving the connection reliability of the connection object parts connected by the conductive material.

[0149] In 100 wt % of the conductive material, the content of the conductive particles is preferably 0.01 wt % or more, more preferably 0.1 wt % or more, and preferably 40 wt % or less, more preferably 20 wt % or less, and further preferably 10 wt % or less. When the content of the conductive particles is above the lower limit and below the upper limit, the conduction reliability between the electrodes is further improved.

[0150] (Connection structure)

[0151] By connecting connection target members using the conductive particles or a conductive material including the conductive particles and a binder resin, a connection structure can be obtained.

[0152] The connection structure has a first connection object part, a second connection object part, and a connection portion connecting the first and second connection object parts, and the connection portion is preferably formed by the conductive particles or formed by a conductive material containing the conductive particles and a binder resin. In the connection structure, the first electrode and the second electrode are preferably electrically connected by the conductive particles. When conductive particles are used, the connection portion itself is conductive particles. That is, the first and second connection object parts are connected by conductive particles.

[0153] Figure 5 In FIG. 1 , a connection structure using conductive particles according to the first embodiment of the present invention is schematically shown in a cross-sectional view.

[0154] Figure 5The connection structure 51 shown has a first connection object member 52, a second connection object member 53, and a connection portion 54 connecting the first and second connection object members 52 and 53. The connection portion 54 is formed by curing a conductive material containing conductive particles 1. Figure 5 In the figure, the conductive particle 1 is shown in a simplified diagram for convenience of illustration. Not only the conductive particle 1 but also the conductive particles 11 and 21 may be used.

[0155] The first connection object member 52 has a plurality of first electrodes 52a on the surface (upper surface). The second connection object member 53 has a plurality of second electrodes 53a on the surface (lower surface). The first electrode 52a and the second electrode 53a are electrically connected via one or more conductive particles 1. Therefore, the first and second connection object members 52 and 53 are electrically connected via the conductive particles 1.

[0156] The method for manufacturing the connection structure is not particularly limited. As an example of the method for manufacturing the connection structure, there can be cited a method in which the conductive material is disposed between the first connection object component and the second connection object component, a laminate is obtained, and then the laminate is heated and pressurized. The pressure of the pressurization is 9.8×10 4 Pa~4.9×10 6 The heating temperature is about 120°C to 220°C.

[0157] Specifically, the connection object component includes electronic components such as semiconductor chips, capacitors and diodes, and electronic components such as circuit substrates such as printed circuit boards, flexible printed circuit boards, glass epoxy substrates and glass substrates. The connection object component is preferably an electronic component. The conductive particles are preferably used for electrical connection of electrodes in electronic components.

[0158] As the electrode provided on the connection object part, metal electrodes such as gold electrode, nickel electrode, tin electrode, aluminum electrode, copper electrode, silver electrode, molybdenum electrode and tungsten electrode can be cited. When the connection object part is a flexible printed circuit board, the electrode is preferably a gold electrode, a nickel electrode, a tin electrode or a copper electrode. When the connection object part is a glass substrate, the electrode is preferably an aluminum electrode, a copper electrode, a molybdenum electrode or a tungsten electrode. It should be noted that when the electrode is an aluminum electrode, it can be an electrode formed only by aluminum, or it can be an electrode having an aluminum layer laminated on the surface of a metal oxide layer. As the material of the metal oxide layer, indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element can be cited. As the trivalent metal element, Sn, Al and Ga can be cited.

[0159] The present invention will be described in detail below with reference to Examples and Comparative Examples. The present invention is not limited to the following Examples.

[0160] In order to obtain the conductive particles, the following substrate particles were prepared.

[0161] Substrate particles A: divinylbenzene copolymer resin particles having a particle size of 3.0 μm (“MICROPEARL SP-203” manufactured by Sekisui Chemical Co., Ltd.)

[0162] Substrate particle B: The only difference from substrate particle A is the particle size, which is 2.5 μm.

[0163] Substrate particle C: Substrate particle having a particle size of 10.0 μm, which is different from substrate particle A only in particle size

[0164] Substrate particles D: core-shell organic-inorganic hybrid particles with a particle size of 3.0 μm (prepared according to Synthesis Example 1 below)

[0165] Substrate particles E: organic-inorganic hybrid particles with a particle size of 3.0 μm (prepared according to Synthesis Example 2 below)

[0166] (Synthesis example 1)

[0167] The surface of divinylbenzene copolymer resin particles ("MICROPEAR LSP-202" manufactured by Sekisui Chemical Co., Ltd.) having a particle size of 2.5 μm was coated with a silica shell (250 nm thick) by a condensation reaction based on a sol-gel reaction to obtain substrate particles D.

[0168] (Synthesis example 2)

[0169] In a 500 mL reaction vessel equipped with a stirrer and a thermometer, 300 g of a 0.13 wt % ammonia solution was added. Next, a mixture of 4.1 g of methyltrimethoxysilane, 19.2 g of vinyltrimethoxysilane and 0.7 g of polysiloxane alkoxy oligomer ("X-41-1053" manufactured by Shin-Etsu Chemical Co., Ltd.) was slowly added to the ammonia solution in the reaction vessel. After hydrolysis and condensation reactions were carried out while stirring, 2.4 mL of a 25 wt % ammonia solution was added, particles were separated from the ammonia solution, and the obtained particles were placed in an oxygen partial pressure of 10 -17 Atm, the mixture was calcined at 350°C for 2 hours to obtain substrate particles E.

[0170] (Example 1)

[0171] After 10 parts by weight of the substrate particles A were dispersed in 100 parts by weight of an alkaline solution containing 5% by weight of a palladium catalyst solution using an ultrasonic disperser, the solution was filtered to remove the substrate particles A. Next, the substrate particles A were added to 100 parts by weight of a 1% by weight solution of dimethylamine borane to activate the surface of the substrate particles A. The substrate particles A whose surfaces were activated were thoroughly washed with water, and then added to 500 parts by weight of distilled water and dispersed, thereby obtaining a suspension (0).

[0172] In addition, a nickel plating solution (1) (pH 8.5) containing 0.14 mol / L nickel sulfate, 0.46 mol / L dimethylamine borane and 0.2 mol / L sodium citrate was prepared. While the suspension (0) was stirred at 60° C., the nickel plating solution (1) was slowly added dropwise to the suspension (0) to perform electroless nickel-boron alloy plating, thereby obtaining a suspension (1).

[0173] Next, a nickel plating solution (2) (pH 8.0) containing 0.14 mol / L nickel sulfate and 0.45 mol / L hydrazine was prepared. While stirring the suspension (1) at 65°C, the nickel plating solution (2) was slowly added dropwise to the suspension (1) to perform electroless nickel plating, thereby obtaining a suspension (2).

[0174] A nickel plating solution (3) (pH 8.0) containing 0.14 mol / L nickel sulfate, 0.09 mol / L sodium stannate trihydrate, and 0.45 mol / L sodium gluconate was prepared. While stirring the suspension (2) at 65° C., the nickel plating solution (3) was slowly added dropwise to the suspension (2) to perform electroless nickel-tin alloy plating to obtain a suspension (3).

[0175] Then, the suspension (3) was filtered to take out particles, which were then washed with water and dried to obtain conductive particles having a Ni—Sn conductive layer (thickness 136 nm) arranged on the surface of the substrate particles A.

[0176] (Example 2)

[0177] A nickel plating solution (pH 8.0) containing 0.07 mol / L nickel sulfate, 0.045 mol / L sodium stannate trihydrate, and 0.225 mol / L sodium gluconate was prepared, and conductive particles were obtained in the same manner as in Example 1 except that this nickel plating solution was used instead of the nickel plating solution (3).

[0178] (Example 3)

[0179] Conductive particles were obtained in the same manner as in Example 1 except that the nickel plating solution (2) and the nickel plating solution (3) were simultaneously added dropwise to the suspension (1).

[0180] (Example 4)

[0181] Conductive particles were obtained in the same manner as in Example 1 except that the nickel plating solution (1), the nickel plating solution (2), and the nickel plating solution (3) were simultaneously added dropwise to the suspension (0).

[0182] (Example 5)

[0183] Conductive particles were obtained in the same manner as in Example 1 except that the nickel plating solution (1), the nickel plating solution obtained by changing the pH of the nickel plating solution (2) to 8.5, and the nickel plating solution obtained by changing the pH of the nickel plating solution (3) to 8.5 were simultaneously added dropwise to the suspension (0).

[0184] (Example 6)

[0185] Conductive particles were obtained in the same manner as in Example 1 except that the amounts of the nickel plating solution (1), the nickel plating solution (2), and the nickel plating solution (3) added were changed to 1.3 times.

[0186] (Example 7)

[0187] Conductive particles were obtained in the same manner as in Example 1 except that the amount of the nickel plating solution (1), the nickel plating solution (2), and the nickel plating solution (3) added was changed to 0.8 times.

[0188] (Example 8)

[0189] A nickel plating solution in which the concentration of sodium stannate trihydrate in the nickel plating solution (3) was changed from 0.09 mol / L to 0.15 mol / L and the concentration of sodium gluconate was changed from 0.45 mol / L to 0.75 mol / L was prepared. The nickel plating solution was used instead of the nickel plating solution (3), and conductive particles were obtained in the same manner as in Example 1.

[0190] (Example 9)

[0191] A nickel plating solution in which the concentration of sodium stannate trihydrate in the nickel plating solution (3) was changed from 0.09 mol / L to 0.30 mol / L and the concentration of sodium gluconate was changed from 0.45 mol / L to 0.90 mol / L was prepared. The nickel plating solution was used in place of the nickel plating solution (3), and conductive particles were obtained in the same manner as in Example 1.

[0192] (Example 10)

[0193] To the suspension (0), 2 g of Ni particle slurry (average particle size 150 nm) was added over 3 minutes to obtain a suspension containing substrate particles to which a core material was attached. Conductive particles were obtained in the same manner as in Example 1 except that the obtained suspension was used. Protrusions were formed on the outer surface of the Ni-Sn conductive layer of the obtained conductive particles.

[0194] (Example 11)

[0195] To the suspension (0), 0.5 g of alumina particle slurry (average particle size 150 nm) was added over 3 minutes to obtain a suspension containing substrate particles to which a core material was attached. Conductive particles were obtained in the same manner as in Example 1 except that the obtained suspension was used. Protrusions were formed on the outer surface of the Ni-Sn conductive layer of the obtained conductive particles.

[0196] (Example 12)

[0197] In the suspension (0), instead of using Ni particle slurry, the precipitation amount was adjusted to partially change when forming the conductive portion to form protrusions. The same procedure as in Example 1 was carried out, except that protrusions were formed on the outer surface of the Ni—Sn conductive layer, to obtain conductive particles.

[0198] (Examples 13 to 16)

[0199] Conductive particles were obtained in the same manner as in Example 10, except that the substrate particles were changed as shown in the following Table 3. Protrusions were formed on the outer surface of the Ni—Sn conductive layer of the obtained conductive particles.

[0200] (Example 17)

[0201] (1) Preparation of insulating particles

[0202] A 1000 mL separable flask equipped with a four-mouth detachable cover, a stirring blade, a three-way valve, a cooling tube and a temperature probe was prepared. In the separable flask, a monomer composition containing 100 mmol of methyl methacrylate, 1 mmol of N,N,N-trimethyl-N-2-methacryloyloxyethylammonium chloride and 1 mmol of 2,2'-azobis(2-amidinopropane) dihydrochloride was weighed into ion exchange water in such a way that the solid content was 5% by weight. Then, the mixture was stirred at 200 rpm and polymerized at 70°C for 24 hours under a nitrogen atmosphere. After the reaction was completed, freeze-dried to obtain insulating particles (average particle size 220 nm, CV value 10%) having ammonium groups on the surface. The obtained insulating particles were dispersed in ion exchange water under ultrasonic irradiation to obtain a 10% aqueous dispersion of insulating particles.

[0203] (2) Preparation of conductive particles

[0204] 10g of the conductive particles obtained by Example 10 were dispersed in 500mL of ion exchange water, 4g of the dispersion was added, and stirred at room temperature for 6 hours. After filtering with a 3μm mesh filter, it was further washed with methanol and dried to obtain conductive particles. When the conductive particles obtained were observed by a scanning electron microscope (SEM), the outer surface of the Ni-Sn conductive layer was coated with insulating particles. By image analysis, the ratio (%) of the coating area of ​​the insulating particles (the projected area of ​​the particle size of the insulating particles) to the surface area of ​​a sphere with a radius of 3.0μm was calculated, and the resulting coverage was 30%.

[0205] (Comparative Example 1)

[0206] Conductive particles were obtained in the same manner as in Example 1 except that the step of electroless nickel-tin alloy plating using the nickel plating solution (3) was omitted and plating was performed instead.

[0207] (Comparative Example 2)

[0208] Conductive particles were obtained in the same manner as in Example 1 except that electroless nickel plating using nickel plating solution (2) and electroless nickel-tin alloy plating using nickel plating solution (3) were previously performed and then electroless nickel-boron alloy plating was performed using nickel plating solution (1).

[0209] (Comparative Example 3)

[0210] A nickel plating solution (pH 8.0) containing 0.14 mol / L nickel sulfate, 1.45 mol / L hydrazine, 0.90 mol / L sodium stannate trihydrate, and 0.60 mol / L sodium gluconate was prepared. The same method as in Example 1 was used, except that electroless nickel-tin alloy plating was performed at 58° C. using the nickel plating solution instead of the nickel plating solutions (1), (2), and (3), to obtain conductive particles.

[0211] (Comparative Example 4)

[0212] A nickel plating solution (pH 8.5) containing 0.14 mol / L nickel sulfate, 1.05 mol / L hydrazine, 0.30 mol / L sodium stannate trihydrate, and 0.30 mol / L sodium gluconate was prepared. The same method as in Example 1 was used, except that electroless nickel-tin alloy plating was performed at 65° C. using the nickel plating solution instead of the nickel plating solutions (1), (2), and (3), to obtain conductive particles.

[0213] (evaluate)

[0214] (1) Distribution of nickel and tin in regions R1 and R2 of the Ni—Sn conductive layer

[0215] Thin film slices of conductive particles prepared using a focused ion beam. The average content of nickel and tin in the entire region of the Ni-Sn conductive layer was determined by ICP-MS. Using a transmission electron microscope FE-TEM ("JEM-2010FEF" manufactured by JEOL Ltd.), an energy dispersive X-ray analyzer (EDS) was used to obtain the average content of nickel and tin in the region R1, the average content of nickel and tin in the region R2, the maximum value of the content of tin in the region R1, and the maximum value of the content of tin in the region R2. In addition, similarly, the content of tin in the region R1 is obtained from the total 100% by weight of tin contained in the entire Ni-Sn conductive layer. In addition, based on the maximum value of the content of tin in the region R1 and the region R2, the region with the maximum value of the content of tin is investigated, and the proportion of the region containing tin is obtained from the thickness 100% of the Ni-Sn conductive layer.

[0216] (2) Initial connection resistance (A)

[0217] The obtained conductive particles were added to "STRUCTBOND XN-5A" manufactured by Mitsui Chemicals, Inc. so as to have a content of 10% by weight and dispersed therein to prepare an anisotropic conductive paste.

[0218] A transparent glass substrate having an ITO electrode pattern with an L / S ratio of 20 μm / 20 μm on the upper surface was prepared. Also, a semiconductor chip having a gold electrode pattern with an L / S ratio of 20 μm / 20 μm on the lower surface was prepared.

[0219] On the transparent glass substrate, the anisotropic conductive paste just prepared was applied in a manner to a thickness of 30 μm to form an anisotropic conductive paste layer. Next, the semiconductor chip was stacked on the anisotropic conductive paste layer in a manner such that the electrodes were facing each other. Then, while adjusting the temperature of the head so that the temperature of the anisotropic conductive paste layer was 185° C., a pressurized heating head was placed on the upper surface of the semiconductor chip, and a pressure of 1 MPa was applied to cure the anisotropic conductive paste layer at 185° C. to obtain a connection structure.

[0220] The connection resistance between the upper and lower electrodes of the obtained connection structure was measured by the 4-terminal method. The average value of the two connection resistances was calculated. It should be noted that the connection resistance can be obtained by measuring the voltage when a constant current flows according to the relationship of voltage = current × resistance. The initial connection resistance (A) was determined according to the following benchmark.

[0221] [Criteria for determining initial connection resistance (A)]

[0222] ○○○: Connection resistance is 2.0Ω or less

[0223] ○○: Connection resistance is more than 2.0Ω and less than 3.0Ω

[0224] ○: Connection resistance is more than 3.0Ω and less than 5.0Ω

[0225] △: Connection resistance is more than 5.0Ω and less than 10Ω

[0226] ×: Connection resistance exceeds 10Ω

[0227] (3) Connection resistance after exposure to acid (B)

[0228] The obtained conductive particles were immersed in an 8% aqueous sulfuric acid solution at room temperature (23°C) for 45 minutes. Then, the particles were taken out by filtration, washed with water, replaced with ethanol and left for 10 minutes to dry the particles, thereby obtaining conductive particles exposed to acid. The obtained conductive particles were used to prepare a connection structure in the same manner as described in (2), and the connection resistance was measured in the same manner as described in the initial connection resistance (A). The connection resistance (B) after exposure to the presence of acid was determined according to the following criteria.

[0229] [Criteria for determining connection resistance (B) after exposure to acid]

[0230] ○○○: Connection resistance B is 1.0 times or more and less than 1.5 times the connection resistance A, and is 10Ω or less

[0231] ○○: Connection resistance B is 1.5 times or more and less than 2.0 times the connection resistance A, and is 10Ω or less

[0232] ○: Connection resistance B is 2.0 times or more and less than 5.0 times the connection resistance A, and is 10Ω or less

[0233] △: Connection resistance B is 5.0 times or more and less than 10 times the connection resistance A, and is less than 10Ω

[0234] ×: Connection resistance B is 10 times or more than connection resistance A, or exceeds 10Ω

[0235] (4) Charge movement in the Ni-Sn conductive layer

[0236] A voltage of 15 V was applied between the mutually insulated measurement terminals of the connection structure obtained by (2) for 500 hours under the conditions of 85° C. and 85% RH. Then, the conductive particles were observed under a microscope (“VHX6000” manufactured by KEYENCE), and whether the metal corrosion in the Ni—Sn conductive layer could be prevented and whether the movement of charges could be prevented was determined based on the following criteria.

[0237] [Criteria for Determining Charge Transfer in Ni—Sn Conductive Layer]

[0238] ○: The conductive layer did not turn black and did not disappear

[0239] ×: A part of the surface of the conductive layer or the entire conductive layer turns black or disappears

[0240] The results are shown in Tables 1 to 4 below.

[0241] [Table 1]

[0242]

[0243] [Table 2]

[0244]

[0245] [Table 3]

[0246]

[0247] [Table 4]

[0248]

[0249] Explanation of symbols

[0250] 1, 11, 21…Conductive particles

[0251] 2…Base material particles

[0252] 3, 12, 22A…Ni-Sn conductive layer

[0253] 11a…protrusion

[0254] 12a…protrusion

[0255] 13…Core Material

[0256] 14…Insulating materials

[0257] 21a, 22a, 22Aa, 22Ba...protrusions

[0258] 22B…Second conductive layer

[0259] 51…Connection structure

[0260] 52…First connection target component

[0261] 52a…1st electrode

[0262] 53…Second connecting object part

[0263] 53a…Second electrode

[0264] 54…Connection

Claims

1. A conductive particle comprising: substrate particles; and A Ni—Sn conductive layer comprising nickel and tin, The Ni—Sn conductive layer is disposed on the surface of the substrate particle. The average tin content in the entire region of the Ni—Sn conductive layer is less than 5% by weight. When the tin content in the thickness direction of the Ni—Sn conductive layer was measured by TEM-EDX, the maximum value of the tin content in the region of 1 / 2 thickness outside the Ni—Sn conductive layer was 5 wt % or more.

2. The conductive particle according to claim 1, wherein When the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, a region at 1 / 2 thickness outside the Ni—Sn conductive layer contains 80 wt % or more of tin out of a total of 100 wt % of tin contained in the entire Ni—Sn conductive layer.

3. The conductive particle according to claim 1 or 2, wherein When the tin content in the thickness direction of the Ni—Sn conductive layer was measured by TEM-EDX, tin was contained in a region of 15% or more of the thickness of the Ni—Sn conductive layer.

4. The conductive particle according to any one of claims 1 to 3, wherein When the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, the Ni—Sn conductive layer contains tin at a content of 5 wt % or more in a region that is 10% or more and less than 50% of the thickness.

5. The conductive particle according to any one of claims 1 to 3, wherein When the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, tin is contained at a content of 5 weight % or more in a region of greater than 10% and less than 50% of the thickness of the Ni-Sn conductive layer, and the maximum value of the tin content in a region of 1 / 2 of the thickness on the outside of the Ni-Sn conductive layer is greater than 5 weight % and less than 40 weight %.

6. The conductive particle according to any one of claims 1 to 3, wherein When the tin content in the thickness direction of the Ni—Sn conductive layer is measured by TEM-EDX, the Ni—Sn conductive layer contains tin at a content of 5 wt % or more in a region that is 30% or less of the thickness of the Ni—Sn conductive layer.

7. The conductive particle according to any one of claims 1 to 3, wherein When the tin content in the thickness direction of the Ni—Sn conductive layer was measured by TEM-EDX, the maximum value of the tin content in the region of 1 / 2 thickness outside the Ni—Sn conductive layer was 10 wt % or more.

8. The conductive particle according to any one of claims 1 to 3, wherein When the tin content in the thickness direction of the Ni-Sn conductive layer is measured by TEM-EDX, tin is contained at a content of 5 weight % or more in an area below 30% of the thickness of the Ni-Sn conductive layer, and the maximum tin content in an area of ​​1 / 2 of the thickness on the outside of the Ni-Sn conductive layer is greater than 10 weight %.

9. The conductive particle according to any one of claims 1 to 8, wherein The conductive particles have a particle diameter of 0.1 μm or more and 1000 μm or less.

10. The conductive particle according to any one of claims 1 to 9, wherein The outer surface of the Ni—Sn conductive layer has a plurality of protrusions.

11. A conductive material comprising: The conductive particle according to any one of claims 1 to 10, and Binder resin.

12. A connection structure comprising: A first connection target member having a first electrode on its surface; a second connection target member having a second electrode on a surface thereof; and a connecting portion that connects the first connection target component and the second connection target component, The connecting portion is formed by the conductive particles according to any one of claims 1 to 10, or is formed by a conductive material containing the conductive particles and a binder resin. The first electrode and the second electrode are electrically connected via the conductive particles.

Citation Information

Patent Citations

  • Conductive particle, conductive material and connection structure body

    JP2015130328A

  • Conductive particles, conductive material and connected structure

    WO2017138521A1